Small-Signal Analysis and Control for a Single-Phase Buck – Boost Inverter - Trần Thị Yến Nhi; Lê Hoàng Minh; Trần Vĩnh Thanh; Phan Thanh Minh; Đỗ Đức Trí (Journal of Technical Education Science, 2026)
This paper presents the configuration of a single-phase buck-boost inverter (1P-BBI), which combines a three-level boost converter (TLB) with a conventional single-phase H-bridge buck inverter. Unlike conventional two-stage topologies, the proposed structure does not require a constant DC-link voltage. The 1P-BBI operates in two modes. In the buck mode, when the input DC voltage is higher than the desired output voltage, only the inverter-stage switches are active to generate the AC output. In contrast, in the boost mode, when the input DC voltage is lower than the output voltage, the switches in the three-level boost converter regulate the DC-link voltage to match the required output level. This paper also presents a small-signal analysis of the 1P-BBI system to establish the transfer function that relates the post-filter output voltage to the input DC voltage. Based on the derived transfer function, the parameters of a Proportional–Integral (PI) controller are selected to regulate the output voltage across the load. Additionally, the paper provides detailed analysis of operating states, circuit calculations, and component selection. Simulation results and experimental verification with a purely resistive load are conducted to validate the proposed control strategy. The experimental results confirm that the inverter is suitable for single-phase applications in the low-to-medium power range.